Main hazard control and hazardous material handling in environment testing laboratory - Saing, Bungaran; Hadita, Hadita; Kustiyah, Elvi; Agustin, Dinda Yesika; Amalia, Rizky Yusrina; Kurnia, Hibarkah (Universitas Mercu Buana, 2023)
The increase in products from chemicals is currently growing rapidly in the Indonesian manufacturing industry. This correlates with a chemical test laboratory that is experiencing a flurry of activity. The placement of chemicals in testing laboratories still does not have problem-solving that can make it easier to search for other potential dangers. So far, the placement of chemicals is not based on hazard, but only on phase differences, namely solid and liquid phases, as well as materials that are frequently and rarely used can pose a hazard. This study aims to provide knowledge about main hazard control to all employees and propose material hazard handling in environmental laboratory testing following the material MSDS. This research method uses the concept of re-layout chemicals in the laboratory based on the type of danger they cause by collecting data obtained from MSDS, literature review studies, references from books, government regulations, and the Merck China website to see the characteristics of chemicals that will be placed in the material stock storage room. This study found a layout mapping of chemicals in the materials storage room, with 3 storage areas and 2 additional storage areas. The result of this research is that Cabinet A is filled with harmless solid phase materials and a class of toxic substances. The chemicals in cabinet B, consist of solid-phase materials that are corrosive, harmless, irritating, carcinogenic, and highly flammable. Whereas on shelf C letter L it consists of liquid phase materials which are harmless, corrosive, dangerous, flammable, highly flammable, highly flammable, carcinogenic or toxic. Whereas Container D contains chemicals that have oxidizing properties and Cabinet E contains chemicals that are highly flammable in water.